Effect of two randomised exercise programmes on bone mass of healthy postmenopausal women. Issue 6611 (5th December 1987) - Chow, R; Harrison, J E; Notarius, C
Abstract : The effect of two structured exercise programmes on the bone mass of 48 healthy postmenopausal white women aged 50-62 was studied after one year. Volunteers were randomised to group 1 (control), group 2 (aerobic exercise), or group 3 (aerobic and strengthening exercises). Before and after the training programme each subject had evaluations of bone mass (determined by neutron activation analysis and expressed as calcium bone index) and maximum oxygen uptake attained on a multistage exercise treadmill test. After one year both exercise groups had higher levels of fitness and greater bone mass than controls. Mean values (2 SEM) for changes in the calcium bone index were -0.011 (0.037), 0.039 (0.035), and 0.066 (0.036) for groups 1, 2, and 3, respectively. Analysis of variance on the observed data and analysis of covariance adjusting changes to the initial mean value for the whole group showed significant differences between each exercise group and the controls but no difference between the exercise groups themselves. Both exercise groups showed a significant improvement in maximum oxygen uptake. This study suggests that exercise may modify bone loss in healthy postmenopausal women.